A systematic review of speech, language and communication interventions for children with Down syndrome from 0 to 6 years. Issue 2 (22nd February 2022) - Seager, Emily; Sampson, Sarah; Sin, Jacqueline; Pagnamenta, Emma; Stojanovik, Vesna
Abstract: Background: Speech and language acquisition can be a challenge for young children with Down syndrome (DS), and while early intervention is important, we do not know what early interventions exist and how effective they may be. Aims: To systematically review existing early speech, language and communication interventions for young children with DS from birth up to 6 years, and to investigate their effectiveness in improving speech, language and communication outcomes in children with DS. Other outcomes are changes in parental behaviour and their responsiveness Methods & Procedures: We conducted a systematic search of relevant electronic databases to identify early intervention studies targeting speech, language and communication outcomes in children with DS published up to May 2020. A total of 11 studies that met the inclusion criteria were synthesized and appraised for quality using the PEDro‐P scale. There were a total of 242 children. We identified three types of intervention: communication training and responsive teaching, early stimulation programme, and dialectic–didactic approach. Main contribution: The findings from nine out of the 11 studies reported positive outcomes for children's language and communication up to 18 months following the intervention. All nine studies reported interventions that were co‐delivered by parents and clinicians. However, there was also a de‐accelerated growth in requesting behaviours in the intervention group reported by one study as well as a case of no improvement for the intervention group. Three studies provided some evidence of improvements to parent outcomes, such as increased parental language input and increased responsiveness. However, there was a moderate to high risk of bias for all studies included. Conclusions: The findings from this review suggest that interventions that have high dosage, focus on language and communication training within a naturalistic setting, and are co‐delivered by parents and clinicians/researchers may have the potential to provide positive outcomes for children with DS between 0 and 6 years of age. Due to the limited number of studies, limited heterogeneous data and the moderate to high risk of bias across studies, there is an urgent need for higher quality intervention studies in the field to build the evidence base. WHAT THIS PAPER ADDS: What is already known on the subject: Speech and language acquisition is usually delayed in children with DS, yet there are currently no standard interventions for children under 6. A number of research‐based interventions exist in the literature, yet it is unknown how effective these are. What this study adds to existing knowledge: This is the first systematic review that specifically and exclusively focuses on parent‐ and non‐parent‐mediated speech, language and communication interventions for children with DS between 0 and 6 years of age. It complements three existing recent reviews, each of which has a slightly different focus. The previously published reviews have covered only parent‐mediated interventions, excluding interventions not mediated by parents, have reviewed interventions including children and adults, without any mention of what early interventions may be like or how effective these may be for young children with DS, have not always assessed risk of bias or have focused specifically on language interventions excluding those focusing on speech articulation or pre‐linguistic skills. The findings from the current review suggest that interventions that have high dosage focus on language and communication training within a naturalistic setting and are co‐delivered by parents and clinicians/researchers may have the potential to provide positive outcomes for children with Diwn syndrome from 0 to 6. We acknowledge that the current evidence base comes from studies with moderate to high risk of bias, hence our conclusions are not definitive. What are the potential or actual clinical implications of this work?: Speech and language therapists will have synthesized information and a quick reference point on what type of interventions exist for children with DS under the age of 6, and evidence of which intervention approaches may be promising in terms of providing positive outcomes. However, it is acknowledged that, due to the limited number of studies and the moderate to high risk of bias inherent in the evidence, there is an urgent need for higher quality intervention studies in the field to build the evidence base.